Головні частоти редукторів портальних тягових мостів - Гутиря, Сергій Семенович; Яглінський, Віктор Петрович; Чанчін, Андрій Миколайович (НТУ "ХПІ", 2016)
На основі запропонованої моделі коливальної системи двопоточного бортового редуктора (ДБР) у складі трансмісії низькопольного тролейбуса розроблено аналітичні залежності визначення пружних деформацій та математичні моделі спектру головних частот системи. За результатами чисельного моделювання побудовано діаграми функцій головних частот від конструктивних параметрів ДБР, виконано порівняння з частотними характеристиками планетарного колісного редуктора (ПКР). Відмічено негативний прояв можливої "квазінульової" жорсткості пружної системи ДБР, що спричиняє зниження першої головної частоти системи та резонансні явища при русі тролейбусів на низьких швидкостях та підвищених навантаженнях трансмісії у режимах розгону-гальмування.

On the basis of the offered model of oscillatory system of the two-line onboard gearbox (TOG) as a part of the driving axles of the low-floor trolleybus analytical dependences of definition of elastic deformations and mathematical models of a range of the main frequencies of system are developed. By results of numerical modeling charts of dependence of the main frequencies on design data of TOG are constructed, comparison with frequency characteristics of the planetary wheel gearbox (PWG) is executed. It is established that for a serial design of TOG type AU-11135 the values of the main frequencies are higher than the corresponding values for PWG type Raba 318/78, and also considerably exceed experimentally established range of a frequency range of vibrations of some of the modern trolleybuses. Negative manifestation of "quasizero" rigidity of the TOR decrease of the first main frequency of oscillating system and to the resonant phenomena at low speeds of the trolleybus movement and the raised moments of loading of transmission on the modes of dispersal and braking is noted. The received results on determination of natural frequencies of TOG provide a theoretical basis for further researches of parametrical and forced fluctuations of driving axles of portal type for the purpose of development of effective methods and means for decrease of their vibration activity as a part of transmission of modern vehicles.
Main frequencies of gearboxes of portal driving axles
Keywords: двопоточний бортовий редуктор; модель коливальної системи; спектр головних частот; ДБР; range of natural frequencies; floating gear wheel